2020
DOI: 10.3390/ijerph17165792
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of PTC Taste Status with Fungiform Papillae Count and Body Mass Index in Smokers and Non-Smokers of Eastern Province, Saudi Arabia

Abstract: Phenylthiocarbamide (PTC) is a bitter compound that is similar in taste to the polyphenols present in most vegetables and fruits. The human taste response towards this compound influences dietary preference, which has a bearing on an individual’s body mass index (BMI). Another factor that influences taste perception is fungiform papillae count. This, in turn, is governed by genetic factors or deleterious habits such as smoking. Establishing a link between all the above factors could lead to a wider understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(40 reference statements)
0
4
1
Order By: Relevance
“…However, our results did not show a different incidence of sinusitis and rhinitis between PTC non-tasters, tasters, and super-tasters. Nor did PTC non-tasters and tasters differ in smoking habits, in contrast with other studies that have observed effects of smoking on PTC thresholds [15,31]. Regarding sex, although it has been suggested that a higher frequency of super-tasters are female [32], no differences were found in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our results did not show a different incidence of sinusitis and rhinitis between PTC non-tasters, tasters, and super-tasters. Nor did PTC non-tasters and tasters differ in smoking habits, in contrast with other studies that have observed effects of smoking on PTC thresholds [15,31]. Regarding sex, although it has been suggested that a higher frequency of super-tasters are female [32], no differences were found in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…(2010) in an Italian cohort of normal weight 20–29-year-old females and males [ 12 ]. Studies carried out in older subjects also report that non-tasters are more likely to have a higher BMI than super-tasters [ 10 , 15 , 33 ]. However, other studies have not found any evidence of a relationship between BMI and PTC taster status [ 11 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 Likewise, body mass index (BMI) was also inversely associated PTC taste sensitivity. 49 Increased sensitivity to certain bitter substances could indicate a lower quantity of vegetable consumption. 40,41 Contrarily, one study found the AVI/AVI non-taster diplotype to be associated with higher risk of obesity in European Americans and Asians, 50 possibly due to differences in nutrient sensing, energy metabolism, immune responses or reduced sensitivity to sweet taste recognition.…”
Section: Obesitymentioning
confidence: 99%
“…7 Individuals sensitive to PTC are also susceptible to more than 10,000 other tastes, which is not observed in individuals who are not sensitive to PTC. 8 The primary gene responsible for PTC sensitivity is TAS2R38, located on chromosome 7. 9 The polymorphisms of the TAS2R38 bitter taste gene may lead to differences in how the taste of food is sensed.…”
Section: Introductionmentioning
confidence: 99%